2009
DOI: 10.1186/1471-2458-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Excess cardiovascular mortality associated with cold spells in the Czech Republic

Abstract: BackgroundThe association between cardiovascular mortality and winter cold spells was evaluated in the population of the Czech Republic over 21-yr period 1986–2006. No comprehensive study on cold-related mortality in central Europe has been carried out despite the fact that cold air invasions are more frequent and severe in this region than in western and southern Europe.MethodsCold spells were defined as periods of days on which air temperature does not exceed -3.5°C. Days on which mortality was affected by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 35 publications
(37 reference statements)
8
121
4
4
Order By: Relevance
“…The longer lagged effect seen for cold-related, all-cause and circulatory-and respiratory-cause mortality is in line with: underlying physiological mechanisms; what has been described in the scientific literature (Armstrong et al 2000;Carder et al 2005;Kyselý et al 2009); and the most widely accepted aetiological hypotheses, which link mortality occurring soonest after a cold wave to diseases of a cardiovascular aetiology, and mortality occurring at the longest lags to respiratory diseases (Ballester et al 1997;Díaz et al 2005). A description of specific-cause mortality related with thermal extremes can be found in a study undertaken by Medina-Ramón et al (2006).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The longer lagged effect seen for cold-related, all-cause and circulatory-and respiratory-cause mortality is in line with: underlying physiological mechanisms; what has been described in the scientific literature (Armstrong et al 2000;Carder et al 2005;Kyselý et al 2009); and the most widely accepted aetiological hypotheses, which link mortality occurring soonest after a cold wave to diseases of a cardiovascular aetiology, and mortality occurring at the longest lags to respiratory diseases (Ballester et al 1997;Díaz et al 2005). A description of specific-cause mortality related with thermal extremes can be found in a study undertaken by Medina-Ramón et al (2006).…”
Section: Discussionsupporting
confidence: 56%
“…Firstly, part of the aetiology of the excess mortality observed after exceptionally cold days is known to be of an infectious nature, whereas the increase seen during heat waves is caused by the direct effects of heat on the metabolism of the individual, provoking generalised decompensation. In the Czech Republic, the greatest increases in mortality have been reported where low temperatures coincided with the presence of the infectious agent (Kyselý et al 2009), and in Holland, no significant associations were observed for respiratory causes in the absence of influenza epidemics, in the period 1979-1997 (Huynen et al 2001). It would therefore seem that the effects of a cold wave are partly influenced by the presence or absence of a pathogenic agent, whose ability to spread is, in turn, favoured by this selfsame drop in temperatures (Hajat and Haines 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Yang et al (2012) and Zhao, Zhu, and Tu (2015) find similar results in subtropical Asia. Kysely et al (2009) find increased cardiovascular mortality in all ages above 25 during cold spells in the Czech Republic. Mortality in nursing homes appears to be sensitive to both hot and cold temperature extremes (Stafoggia et al 2006;Hajat, Kovats, and Lachowycz 2007).…”
Section: Introductionmentioning
confidence: 74%
“…For instance, a study conducted in England and Wales found an association between cold temperature and mortality [10]. Also, in central Europe, it was observed an increased mortality with temperature at low average daily temperatures [11]. Ireland also experiences increased cold-related mortality [12].…”
Section: Resultsmentioning
confidence: 99%